1998
DOI: 10.1002/(sici)1097-4547(19980101)51:1<76::aid-jnr8>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previously, by using in vivo microdialysis, we demonstrated a huge release of 45Ca2+ from prelabeled tissues to dialysate that was evoked by application of N-methyl-D-aspartate (NMDA) to the rat dentate gyrus (DG) and sector 4 of the cornu ammonis. To establish the mechanism of this phenomenon, in the present study, we characterized its NMDA receptor dependence, investigated the mechanism of 45Ca2+ removal from the cells, and evaluated the possible involvement of calcium-binding protein calbindin D28k and of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Several studies have demonstrated that amiloride has neuroprotective properties using a dose of 10 mg/kg [27,[52][53][54]. Following this logic, we hypothesized that GCI-induced hippocampal damage can be protected by reducing intracellular zinc accumulation through inhibition of NHE-1 [27,55].…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have demonstrated that amiloride has neuroprotective properties using a dose of 10 mg/kg [27,[52][53][54]. Following this logic, we hypothesized that GCI-induced hippocampal damage can be protected by reducing intracellular zinc accumulation through inhibition of NHE-1 [27,55].…”
Section: Discussionmentioning
confidence: 93%
“…Po powrocie stacji do nadawania w kwietniu 1982 r. z ramówki zniknęło wiele luźniejszych tematycznie pozycji, na czele z utrzymywanym w klimacie satyrycznego komentarza wydarzeń krajowych magazynu "60 minut na godzinę". Audycja "Zapraszamy do Trójki" przeszła zmianę formatu, odrzucając formułę sprzed uchwalenia stanu wojennego, przechodząc z pasma audycyjnego (kilku miniaudycji w ciągu dnia) na magazyn informacyjny nadawany "na żywo", z udziałem (łączących się telefonicznie) słuchaczy 21 . W tym samym roku na antenie radiowej Trójki debiuty radiowe zaliczyli: Marek Niedźwiecki -jeden z najsłynniejszych prezenterów w historii Polskiego Radia i autor sztandarowego programu rozgłośni ("Listy przebojów Programu Trzeciego", której premierowa emisja nastąpiła 24 kwietnia 1982 r. 22 ) oraz Tomasz Beksiński, charyzmatyczny znawca kultury anglojęzycznej i prowadzący audycję "Nowa Płyta" 23 .…”
Section: Program Trzeci Polskiego Radia - Dzieje Stacjiunclassified